Analysis of Carbohydrates from Ficus benghalensis (Linn.) - M. Shah, Sapana; R. Deshmukh, Madhvi; R. Katade, Sushama; R. Deshpande, Nirmala (Asian Journal of Chemistry, 2016)
Ficus benghalensis (L.) is a medicinal plant. In Ayurveda its use in diabetes is mentioned. The aerial root of the plant is used as a drug. Therefore the analysis of carbohydrates of aerial roots has been carried out using the technique of paper chromatography. This data provided some interesting results.